(untitled) - Agarwal, Ravi P. (Cambridge, UK, 2001)
This book provides a clear exposition of the flourishing field of fixed point theory and explores many applications of the theory to analysis, with topological considerations playing a crucial role. The very extensive bibliography and close to 100 exercises
Keywords: Lý thuyết điểm cố định,Lập bản đồ (Toán học),Fixed point theory,Mappings (Mathematics)